(3JNQjL GdOdGdGJ GdSeYjI Ydi eG cGf aj YgO QShd Gddg Udi Gddg Ydjg hSde ef GdMQa hGdUfGFY hGdYeGdGJ GdTQYjIs - (3CHh GdMSf Ydj Hf eMeO Hf CMeO Hf ehSi Hf eSYhO Hf CHi ZaQI GdNRGYi GHf Pi GdhRGQJjfs; (3GHf XgjQI , eMeO Hf eMeO Hf CHj HcQ Hf Ydj Gdecj GdeNRhej, LeGd GdOjf,J (B986 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdNdb ef ZjQ EaJbGQ Edjge hHYO , aEfi deG QCjJ cKjQkG eef de JQSN ai GdeYGQa bOeg ai Cf CLeY eG JCOi ai Ydeg ef Jdc GdYeGdGJ ai cJGH jhVM fTQgG s
(3BNQgG (B:s
(3ahGFO dZhjI ai CQHY eSGFd hai GdUMGM (B: (3bHQJ GdejJ CbHQg hCbHQg bHQkG Ci (B: (3OafJg , hCbHQJg Ci CeQJ Cf jbHQ hGddMO ai GdLGfH , hGddMO gPG BNQ eG hLO ef gPG GdcJGH GdaP GdfGOQ s
(3Yf fSNI HGdeYgO GdRjJhfi HJhfS HQbe (B1572s
(3ai GdeYgO fSNI CNQi HQbe (B158 (3JGQjNs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs